Libya: the “new war” for economic power - Miguel García Guindo; Beatriz Mesa García (Revista CIDOB d'Afers Internacionals, 2015)
This article addresses the current situation in Libya from a perspective that takes as its reference the importance of energy resources as a recurrent element in the political instability and configuration of the Libyan state in its recent history. For this it deals, first of all, with the debate on the importance of economic factors in explaining the roots of the conflict. Secondly, it analyses the current disposition of the various centres of power in relation to the control of the country’s sources of wealth; and, to conclude, it reveals the challenge the fight to control hydrocarbons poses to the achievement of a political process.